Ultrasound-Guided Treatment of Peripheral Nerve Pathology - Dettori, Nathan; Choudur, Hema; Chhabra, Avneesh (Seminars in Musculoskeletal Radiology, 2018)
High-resolution ultrasound serves as a fast, accessible, reliable, and radiation-free tool for anatomical and dynamic evaluation of various peripheral nerves. It can be used not only to identify and diagnose peripheral nerve and perineural pathology accurately but also to guide various nerve and perineural interventions. We describe the normal and pathologic appearances of peripheral nerves, the pathologies commonly affecting the individual peripheral nerves, and the current ultrasound-guided peripheral nerve interventions and techniques. Future directions are also highlighted.
Keywords: ultrasound; peripheral nerve; intervention; ablation; nerve entrapment